Legal Review of the Eradication of Criminal Acts of Corruption in Indonesia Based on Legal and Moral Approaches - Ritian Handayani; Yasmirah Mandasari Saragih (International Journal of Sociology and Law, 2025)
This article proposes to review the handling of corruption cases in terms of juridical and morality in Indonesia. This study is a normative legal study with descriptive analysis. This study uses a philosophical approach and a conceptual approach to determine the efforts made by the government to overcome corruption in Indonesia from the juridical and moral aspects of the Indonesian people based on the Pancasila Ideology. Efforts to eradicate corruption have not been able to be overcome optimally because they are spread sporadically in Indonesia. Obstacles are occurring structurally, culturally, instrumentally and management. Prevention and eradication of corruption must be emphasized as the moral responsibility of the Indonesian people. Because it will be one of the biggest threats to the existence of the Indonesian nation. Prevention of corruption must be carried out systematically by strengthening regulations and conducting international cooperation on the issue of corruption as a crime against Human Rights throughout the world, especially in Indonesia. That aspect of law enforcement in eradicating criminal acts of corruption requires the role of all parties involved in achieving the target of eradicating corruption that is rampant in Indonesia, there are four factors causing corruption; political and legal factors, historical factors, social factors and cultural factors, and economic factors. Concrete solutions in eradicating corruption are needed by Indonesia to redesign public services, strengthen transparency, supervision and sanctions against government activities related to the economy and human resources, increase the empowerment of supporting instruments in preventing corruption and to ensure that law enforcement is free from corruption. The strategy to eradicate corruption must be built with the will of all parties who want to eradicate corruption itself, by not giving the slightest tolerance in the act of corruption itself. In realizing an effort to eradicate corruption itself, it requires determination in meeting the prerequisites in terms of existence driven by political ability and will and a strong commitment from all parties, transparent and accountable in its implementation, available and balanced resources and capacity.